MOTIVASI PERLINDUNGAN HUTAN PADA MASYARAKAT DI KAWASAN HUTAN LINDUNG GAWALISE KECAMATAN BANAWA TENGAH KABUPATEN DONGGALA (STUDI KASUS DI DESA POWELUA) - Muller, Kaleb; Golar, Golar; Ihsan, Moh. (Universitas Tadulako, 2015)
Forest is an area grown with heavy tress and other plants. It gives big benefit for human life start from water system manager, world lungs up to industry activity. Powelua village is one of villages lies in Central Banawa sub distric of Donggala Regency. Central Sulawesi Province has conservation forest. The existence of the forest has been known by the whole society of the village and there are even some people utilize it as herbal plants derived from the forest. The research aims to find out the motivation of the forest protection that conducted by society to protect Gawalise conservation forest in Powelua village, Central Banawa sub district, Donggala Regency. This research employed descriptive method trough stages of collecting primary and secondary data where those data were obtained from direct interview to the respondents and other supporting data from village government and literature review by using scale 1-3-5 (Likert Modification) then it would get conclusion of how far the motivation on forest protection of the society in Gawalise conservasition forest. Ecology motivations is still dominant compared to economy and social motivation in the effort of Gawalise preservation forest. It is encouraged by a strong willingness to defend the conservation are, including the conservation forest. The way done by the society of Powelua in conservasing the forest is replanting the forest begin from the part of degradation and forming village rules about activities related to conservation forest. Key words : Motivation, Protection, Conservation Forest